PREVALENCE OF SEDENTARY PEOPLE AND NUTRITIONAL STATUS IN SCHOOL EDUCATION NETWORK EAST COUNTY PUBLIC STATE EDUCATION OF PIRIPIRI-PI (Fiep Bulletin - online, 2016)
The increase in sedentary lifestyle worldwide and Brazil have contributed to the increase in chronic degenerative processes such as heart disease, diabetes and cancer. The aim of this research was to determine the prevalence of physical inactivity and relate the level of sedentary lifestyle and nutritional status of schoolchildren from the High School of State Public Network municipality of Piripiri-PI. The study was cross-sectional, descriptive, which were evaluated 210 schoolchildren of both sexes, with average age of 15.5 ± 1.1, enrolled in the public network State concoction-PI school. For data collection was carried out anthropometric measurements and questionnaires to identify the level of physical activity. The statistical analysis was applied to descriptive statistics with average procedures ± standard deviation for sample characterization and Chi - square test for association between sex and all variables and level of physical activity and nutritional status (p
Keywords: Sedentary lifestyle; School; Nutritional status.